Pengembalian kredit dan pendapatan petani plasma pir-trans kelapa sawit=(Kasus di Kecamatan Tungkal Ulu Kabupaten Tanjung Jabung Propinsi Jambi) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
This research aimed to investigate the ability of farmers to return credits, the income of farmers and constraints to improve the performance of Pir-Trans Kelapa sawit. The research found that the farmers had enough abilities to return their credits. The abilities to return credit and the income of farmers varied among farmers group, depended on the age of crops. In average, the farmers could return their credit Rp 163,232/month. The average of farmer's income of palm oil crops was Rp 380.874/month gross or Rp 224.821/month net income. The minimum target of transmigran's income Rp 3.500.000/year in the 5th years could be reached by Pir-Trans Kelapa Sawit program. Four years after conversion, the farmers had Rp 418.596/month or Rp 5. 023.152/year net income of palm oil crops. The research suggested to increase the productivity of palm oil crops in order to utilized the full capacity of machine.